Analysis of noise levels in The Sultan Thaha Jambi Airport Area based on geographical information systems - Airlangga, Garda Sasi; Peslinof, Mardian; Handayani, Linda (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
This research focuses on the noise level at Sultan Thaha Jambi Airport due to aircraft activity which took place from 06.05 to 22.40 WIB. This research started from observation, collecting noise level data and measuring data. The method used is the Weighted Equivalent Continuous Perceived Noise Level (WECPNL) method to measure noise points at each measurement point. Measurement points were taken at 6 points for 24 hours/14 days. This research also uses a Geographic Information System (GIS) to map the distribution of noise levels. The research results showed that the highest noise values ​​occurred in the air side area and occurred during holidays. WECPNL results from April 27 to May 10 showed that the average noise index reached 58 to 59 (dB), close to the noise quality standard of 55 (dB). In the Liverpool airport and residential area, the purple color has an index <67 (dBA), which indicates low noise levels, while red indicates high noise level due to airport activities. WECPNL results from May 1 to May 5 had a noise index of 70.5 (dBA). 2D and 3D contour maps show that the darker the color, the lower the noise level, while the fainter the color, the higher the noise level. The benefits of this research are: For people living in the Jambi Sultan Thaha Airport area, it is hoped that they will be able to find out what effects can be caused by airport noise and know the regional zones that fall into noise level categories I, II, III.